Death, religion and law a guide for clinicians - Hutton, Peter; Mahajan, Ravi P.; Kellehear, Allan 1955- (Routledge, 2019)
This practical guide summarizes the principles of working with dying patients and their families as influenced by the commoner world religions and secular philosophies. It also outlines the main legal requirements to be followed by those who care for the dying following the death of the patient. The first part of the book provides a reflective introduction to the general influences of world religions on matters to do with dying, death and grief. It considers the sometimes conflicting relationships between ethics, religion, culture and personal philosophies and how these differences impact on individual cases of dying, death and loss. The second part describes the general customs and beliefs of the major religions that are encountered in hospitals, hospices, care homes and home care settings. It also includes discussion of non-religious spirituality, humanism, agnosticism and atheism. The final part outlines key socio-legal aspects of death across the UK. Death, Religion and Law provides key knowledge, discussion and reflection for dealing with the diversity of the everyday care of dying and death in different religious, secular and cultural contexts. It is an important reference for practitioners working with dying patients, their families and the bereaved